FEASIBILITY TEST OF 21ST CENTURY CLASSROOM MANAGEMENT THROUGH DEVELOPMENT INNOVATION CONFIGURATION MAP - Herfina, Elly Sukmanasa (Universitas Pakuan, 2022)
This study aims to determine the feasibility of classroom management in 21st century learning through the development of innovation configuration maps. 21st century learning provides opportunities for teachers to innovate to increase success in learning. Teachers can describe the 21st century learning environment, through the development of innovation configuration maps. This study used a quasi-experimental method with students in class using maps to develop IC maps based on the Caring-Based Adoption Change Model (CBAM). The results show that 21st century skills can be realized in learning environments through content-based and project-based approaches, but equally important is having 21st Century Ecology.